Understanding the integration of deep learning and artificial intelligence in Quranic education and research through bibliometric analysis - Nirwana An, Andri; Tamami, Fauziyah Qurrota A’yun; Daud, Zainora; Mohd Salleh, Norsaleha; Ishak, Mohamad Haeqal; Muthoifin, Muthoifin (Educational Process: International Journal (EDUPIJ), 2025)
Background/purpose. Recent developments in information and communication technology have opened up many new opportunities in various research fields, including religious studies (Burton, 2020). One of the most notable innovations was integrating artificial intelligence and deep learning in religious studies, including Quranic education and research. This study conducted a bibliometric analysis of Quranic education and research integrating deep learning and artificial intelligence. The study evaluated five key indicators in bibliometrics: scientific production, authors, country level, affiliations, and sources or journals.